(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Eco feminist interpretation of Toni Morrison’s novels: Sula & TheBluest Eye. The present paper aims at the study of Toni Morrison’s novels withan Feministic approach. IT is based on the study of three novels The Sula &The Bluest Eye. It shows how women and nature are related to each other and howboth are oppressed by the patriarchal society in the same way and how women andnature both are showing resistance towards this dominance in their own ways.All the female characters in these novels are related and affected by nature inone or other ways. This oppression is still there in the contemporary period.